Situasi Pemenuhan Hak Anak Yang Berkonflik Dengan Hukum Di Lembaga Pemasyarakatan/Rumah Tahanan Dewasa: Studi Kasus Di Sidoarjo Dan Surabaya, Jawa Timur - Endah Triati (Jurnal Transformasi Administrasi, 2018)
Prisons are not a good place for children, even for Children in Conflict with the Law (ABH Actors). For some reasons, there are still children who is faced with the law placed in adult prisons (Penas) or Detention Centers (Rutan), one of which is in Sidoarjo Prison or Rutan Surabaya, East Java. Placement of them in Adult Prisons / Detention is a challenge in realizing restorative justice for ABH. The diversionary spirit for ABH which is part of the adjudication process is still constrained in some parts. Efforts to lead to restorative justice still find obstacles, placement of ABH in Adult Prison / Rutan is one of them. Thie aim of this study tries to see the situation of the fulfillment of the rights of the child who is faced with the law in the prison and the detention centers. There are four main dimensions of child rights fulfillment, namely 1). Right to life, 2). Right to survival and development, 3). Right of protection and, 4). Right of participation. Qualitative methood choosed in this study, who are involved four ABH informants. The results of this study indicate that in the fulfillment of the right to life, the informant complained about the fulfillment of food nutrition. Similarly, the fulfillment of the right to survival and development is also complained by informants, but informants give appreciation for the aspect of religious education is considered good. Related to the protection rights that are also still complained by informants is, the existence of discrimination and neglect, which continues to decrease sense of security. While in terms of fulfillment of the right to participate, some informants feel enough, some feel less.